Square footage requirement of weaned pigs - B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1983)
One hundred and twenty weaned pigs were used to evaluate the effect of space allowance. Pigs were housed in a control environment nursery with woven wire flooring with 4, 6, 8, 10, or 12 head per 4' x 5' pen which allowed 4.5, 3.0, 2.25, 1.8, and 1.5 square feet of usable space, respectively, for each pig. No significant differences were observed in performance for the five-week period. However, during week 3,4, and 5 of the trial, pigs with 1.8 and 1.5 sq. ft. of space, respectively, had a markedly reduced feed intake and average daily gain. Feed gain ratios were not affected. This study suggests a minimum of 2.25 sq. ft. will support pig performance equal to those pigs allowed more space for the 5-week period.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Weaned pigs; Housing